MODEL PARTISIPASI MASYARAKAT MOI DALAM PELAKSANAAN PENDIDIKAN ADAT KAMBIK (Studi Kasus Tentang Kelangsungan Pendidikan Kambik Di Suku Moi Kampung Maladofok Kabupaten Sorong). - Heriyanti, Yuliana, (Universitas Muhammadiyah Sorong, 2018)
The purpose of this study was to reveal the Participation of the Moi Community in Kambik Education (Indigenous Education) in Maladofok Village, Sorong Regency. Kambik education is a Moi tribal education system in Sorong, West Papua. Kambik education (Moi tribal customary education) learns about leadership, learns the customs of the Moi tribe, traditional medicine, and understands human existence. Various problems began to emerge in the life of the state, the demand for revival and reviving the values of local wisdom into an alternative. So it is important in this research, the researcher raises two issues that have been formulated in the question. First: What is the participation of the Moi community in the Kambik education process ?, and Second; to what extent are the values taught in Kambik's education in social life? This question is important to be formulated as the power of data which then becomes a reference in education policy that raises local potential. The research uses a qualitative approach. Researchers conducted in-depth interviews at the research location, more points than the ethnographic method itself is that researchers conduct research and also get meaningful education from the lives of local people. The results of this study are to encourage the acceleration of development in Sorong Regency. Because in addition to the academic interests, the Moi tribe Kambik (traditional education) education is a new alternative form of humanity awareness in the Moi tribe of Sorong Regency. The results of this study could be a recommendation and input for the Sorong Regency government to plant the values of Kambik education itself in the generation of indigenous Moi children in Sorong Regency in particular and the Moi generation in general. The results of the study are, First: project files for alternative education design in Sorong Regency or can be synergized with a special curriculum.